Portulaca oleracea inhibit vincristine induced peripheral neuropathy: involvement of ATP-sensitive K+ channels - Rupa, L. Mohana; Mohan, K.; Kumar, N. Santhosh (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The Portulaca oleracea belonging to portulacaceae family. It is a herbaceous plant widely distributed throughout the world and used in traditional medicine for many ailments. The present study was to evaluate the antinociceptive action of petroleum ether extract of P. oleracea in vincristine induced peripheral neuropathic pain and the possible mechanisms involved. Methods: Peripheral neuropathy was induced in rats by administration of vincristine sulfate (50 μg/kg i.p.) for 10 consecutive days. The cold tail hyperalgesia was assessed by cold water tail immersion test. To identify the possible mechanisms involved in the antinociceptive action of petroleum ether extract of P. oleracea, acetic acid writhing method was employed. Mice were pretreated with naloxone, glibenclamide before petroleum ether extract treatment to identify the involvement of opioid and potassium channels, respectively. Results: The administration of petroleum ether extract of P. oleracea (100 and 200 mg/kg p.o.) for 10 days significantly attenuated vincristine-induced cold hyperalgesia. Pre-treatment with glibenclamide reversed the antinociceptive effect of P. oleracea, but the naloxone pre-treatment did not reverse the antinociceptive activity of P. oleracea. Conclusion: The results of the present study reveal the antinociceptive effect of P. oleracea in vincristine induced peripheral neuropathy and involving ATP-sensitive potassium channels pathway.